The future is now: Climate displacement and human rights obligations—a note on recent developments in the UN Human Rights Committee - Thornton, Fanny (Frontiers in Climate, 2022)
Although climate litigation – or the pursuit of legal resolve of matters stemming from anthropogenic climate change – has been growing around the world, climate mobility is seldom at the heart of relevant case law. It is human rights law bodies, in particular, which have nevertheless begun to progress legal developments in the sphere of climate mobility. This note looks at a 2022 determination by the UN Human Rights Committee concerning the habitability of a small island setting – Australia’s Torres Strait Islands – under climate change conditions and the legal responsibilities of nation states to abide by their international human rights obligations in implementing timely adaptation measures now which could help to ensure continued habitation.